Seasonal dynamics of dissolved iron in the marginal ice zone of South Atlantic and Southern Oceans - Jansen van Vuuren, Lide (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.